A multidimensional overview of the burden of psoriasis. (19th July 2018) - Griffiths, C.E.M.; Jo, S.‐J.; Naldi, L.; Romiti, R.; Guevara‐Sangines, E.; Howe, T.; Pietri, G.; Gilloteau, I.; Richardson, C.; Tian, H.; Augustin, M.
Summary: Psoriasis is a common, chronic, inflammatory skin disease which affects between 0.09% and 11.4% of the population worldwide. It causes symptoms such as itch and skin pain, but its effects can actually extend beyond the skin. It is often associated with additional co‐occurring diseases (comorbidities) such as cardiovascular disease, psoriatic arthritis (PsA), obesity, diabetes and anxiety or depression. Altogether psoriasis can cause significant negative impact on the quality of life (QoL) as well as work productivity of psoriasis patients. Additionally, the presence of common and bothersome symptoms such as itch and psoriasis lesions on different body areas can further increase the burden of disease on patients. In this large and multinational survey of dermatologists and their psoriasis patients, we estimated the incremental burden of comorbidities, itch, and affected body areas among patients with moderate to severe psoriasis. Anonymised responses were collected from 524 dermatologists and 3, 821 psoriasis patients across 9 countries (UK, France, Germany, Spain, Italy, Russia, South Korea, Mexico and Brazil) using questionnaires and analysed to assess the impact of psoriasis on patients. Questionnaires collected data regarding psoriasis symptoms (presence/extent of itch, sleep disturbance due to itch, presence of skin pain), QoL and medical resource utilisation in the past 12 months (e.g. number of consultations that patients had with their dermatologist and number of hospitalisations). Overall, the results indicate that the presence of physical and psychological comorbidities, symptoms such as itch, presence of psoriasis lesions especially on visible (e.g. scalp, face, hands) and sensitive areas (e.g. genitals, scalp, face) significantly affect psoriasis patients' QoL and cause significant financial burden due to work productivity impairment and increased usage of medical resources. Abstract : Linked Article:  Griffiths et al. Br J Dermatol 2018;179 :173–181